Total quality strategy in the formative process of the occupational physician - Franco, Giuliano; Bisio, S. (Scandinavian Journal of Work, Environment & Health, 1999)
Interest in applying the concepts of total quality management to the fields of health care and medical education is growing. This paper analyzes the field of education in occupational medicine to explore the relationships between teaching and the deliverance of a product or a service. Issues such as defining teaching customers, addressing customer needs, teaching processes, and assessing and improving quality teaching are described. The occupational physician is requested to act according to particular competencies. This demand implies the need to meet specific requirements. To assure the achievement of these goals, the implementation of a teaching process must include (i) targeting the learning objectives (the knowledge, skills, and attitudes the specialist should have), (ii) planning the evaluation system (ability of the course to assure the achievement of the objective), (iii) evaluating the curriculum (compliance of the acquired competencies to the needs).
Keywords: competencies; continuous improvement; occupational health physician; process management; quality assurance; system control; training objective; training system